Effects of wildfire and post-fire salvage logging on rainsplash erosion in a semi-arid pine forest of Central Eastern Spain. (1st March 2023) - de Pagter, Tijs; Lucas-Borja, Manuel Esteban; Navidi, Mehdi; Carra, Bruno Gianmarco; Baartman, Jantiene; Zema, Demetrio Antonio
Abstract: Rainsplash erosion on forested hillslopes can be increased by both wildfires and post-fire salvage logging, especially under semi-arid Mediterranean conditions. However, few studies have compared rainsplash erosion among forest sites impacted by logging to other forest areas. To fill this gap, this study has evaluated surface runoff and soil erosion in a burnt and logged (manually or mechanically) pine forest of Central-Eastern Spain under simulated rainfall and compared it to unlogged and unburnt plots. Compared to the unburnt plots, surface runoff significantly increased (over 150%) in logged areas, with a peak of 220% on the areas directly subjected to logging machinery. Peak runoff was substantially increased by fire (+130%) and less by logging (+8. Soil loss due to rainsplash erosion was about 235% (manual logging) to 750% (mechanical logging) higher compared to the unburnt plots. Wildfire exerted a much higher soil disturbance compared to salvage logging, with a soil hydrological response that can be up to an order of magnitude higher. The increased runoff and erosion rates in response to wildfire and logging were ascribed to soil compaction, which increased on average 60% on logged plots as well as to the removal of vegetation cover (−80%), whereas soil roughness played a minor role. From these results, we suggest using lightweight machinery in burnt soils, to reduce surface runoff and erosion. The possibility of building contour felled log debris using the burnt wood may also be considered, in order to retain the eroded sediments. Highlights: Runoff increases up to 220% on areas impacted by logging machinery. Peak runoff and time to peak were increased by both fire and logging. Rainsplash erosion on the skid tracks was up to 750% higher than in unburnt sites. The increased runoff and erosion were mainly ascribed to soil compaction in logged areas. Lightweight machinery or construction of contour felled log debris are suggested in burnt areas.